5-HT2B Receptor Antagonists Inhibit Fibrosis and Protect from RV Heart Failure. (1st February 2015) - Janssen, Wiebke; Schymura, Yves; Novoyatleva, Tatyana; Kojonazarov, Baktybek; Boehm, Mario; Wietelmann, Astrid; Luitel, Himal; Murmann, Kirsten; Krompiec, Damian Richard; Tretyn, Aleksandra; Pullamsetti, Soni Savai; Weissmann, Norbert; et al.
Abstract : Objective . The serotonin (5-HT) pathway was shown to play a role in pulmonary hypertension (PH), but its functions in right ventricular failure (RVF) remain poorly understood. The aim of the current study was to investigate the effects of Terguride (5-HT2A and 2B receptor antagonist) or SB204741 (5-HT2B receptor antagonist) on right heart function and structure upon pulmonary artery banding (PAB) in mice. Methods . Seven days after PAB, mice were treated for 14 days with Terguride (0.2 mg/kg bid) or SB204741 (5 mg/kg day). Right heart function and remodeling were assessed by right heart catheterization, magnetic resonance imaging (MRI), and histomorphometric methods. Total secreted collagen content was determined in mouse cardiac fibroblasts isolated from RV tissues. Results . Chronic treatment with Terguride or SB204741 reduced right ventricular fibrosis and showed improved heart function in mice after PAB. Moreover, 5-HT2B receptor antagonists diminished TGF-beta1 induced collagen synthesis of RV cardiac fibroblasts in vitro . Conclusion . 5-HT2B receptor antagonists reduce collagen deposition, thereby inhibiting right ventricular fibrosis. Chronic treatment prevented the development and progression of pressure overload-induced RVF in mice. Thus, 5-HT2B receptor antagonists represent a valuable novel therapeutic approach for RVF.